Consumer Skepticism of Claims in Food Ads vs. on Food Labels: An Exploration of Differences and Antecedents. Issue 4 (24th January 2019) - Mitra, Anusree; Hastak, Manoj; Ringold, Debra J.; Levy, Alan S.
Abstract : Considerable evidence shows that consumers are skeptical of advertising, that is, have a tendency to doubt the truth of advertising claims. The main focus of our paper is to explore, in the context of food products, whether this typically high level of skepticism is also exhibited for product labels. In addition, we look at consumer skepticism associated with health claims in food ads and labels as well as with the Nutrition Facts Panel on food packages. Finally, we examine some individual difference factors that might influence consumer skepticism. We report the results of a large‐scale survey designed to explore these issues, and we discuss the implications of our findings for public policy and future research.